2020
DOI: 10.1038/s41598-020-75136-z
|View full text |Cite
|
Sign up to set email alerts
|

Stainless steel weld metal enhanced with carbon nanotubes

Abstract: This paper aims to establish the most indicated route to manufacture a nanostructured powder composed of 5 wt% Multi-walled Carbon Nanotubes and 304LSS powder. Four specimens were prepared using Mechanical Alloying and Chemical Treatment (CT) with Hydrogen Peroxide ($${\mathrm{H}}_{2}{\mathrm{O}}_{2}$$ H 2 O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 66 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…The microhardness percentages were calculated based on indentation data in topside and cross-section of WM with nanocomposite compared to its own BM. Although they using the same process, the WM/BM welding with similar materials, 6,7,13 not is appropriately compared with our results, because our WM/BM were a dissimilar materials. However, despite that is evident the reinforcement effect of the CNTs in the weld metals.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The microhardness percentages were calculated based on indentation data in topside and cross-section of WM with nanocomposite compared to its own BM. Although they using the same process, the WM/BM welding with similar materials, 6,7,13 not is appropriately compared with our results, because our WM/BM were a dissimilar materials. However, despite that is evident the reinforcement effect of the CNTs in the weld metals.…”
Section: Resultsmentioning
confidence: 55%
“…Recently, Borges et al 13 reported a microhardness increase up to 40% in the cross-section, if compared with compared to a SS 304L without CNTs clad welded by GTAW process. Moreover, this work indicates the presence of carbide formation in the microstructure of SS 304L-CNT composite, which may be responsible for grain refinement.…”
Section: Introductionmentioning
confidence: 99%
“…4. The nanostructured powder evidenced a reduction in the intensity of the austenitic plane (111), in part due to the superposition with C(100) of the carbon nanotubes, and to the high X-ray absorption capacity of the latter, while the peak C(002) can already is be noted in the spectrum 9,10,34 . All of this proves that the nanostructured powder (304LSS-CNT) was introduced efficiently in the melting aluminum to supply elements alloys such as Fe, Cr, Ni, and Mn of the stainless-steel particles, and nanofibers (MWCNT); to improve both the mechanical properties and electric conductivity 8,12 .…”
Section: Resultsmentioning
confidence: 99%
“…2e) changed the aluminum's microstructures, creating elongated grains, with a low segregation of the Fe and of the other elements in the dendrite's limits 33 . This behavior could be associated with the combination of a decreasing of the grain size by effect to the stainless-steel particles and a uniform distribution of the carbon nanotubes in the MM, which avoids a bigger movement of the atoms by the effect of the pine with mainly Cr and Ni whose carbon affinity is great 10,17 . When the percentage of SS increase to 2 wt.% (e, j), along 0.1wt.% CNT, the microstructure was remarkably altered but no segregation was observed, as the temperature of the liquid aluminum was not enough to melt all the SS particles, which produced a deterioration of the properties of this sample 33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation